1986
DOI: 10.2957/kanzo.27.417
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neonatal thymectomy on experimental autoimmune hepatitis in mice.

Abstract: Using an autoimmune hepatitis model of A/J mice which was prepared with immunization by syngeneic crude liver proteins, various influences of neonatal thymectomy were studied by observations of histological liver changes, autoantibody to liver-specific membrane lipoprotein (LSP), delayed-type hypersensitivity (DTH) to LSP, and purified protein derivative (PPD), and suppressor activity to LSP. The liver changes in the thymectomized mice were more intense than those in the non-thymectomized controls. Production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…The transient liver damage produced in these models was characterized by perivascular infiltrates, mononuclear portal infiltrates and lobular hepatitis [98]. Antibodies to liver-specific proteins were produced; liver-specific T-cell responses were demonstrated; and counter-regulation of the autoreactive response by the thymus was recognized (TaBle 1) [99].…”
Section: Inbred Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transient liver damage produced in these models was characterized by perivascular infiltrates, mononuclear portal infiltrates and lobular hepatitis [98]. Antibodies to liver-specific proteins were produced; liver-specific T-cell responses were demonstrated; and counter-regulation of the autoreactive response by the thymus was recognized (TaBle 1) [99].…”
Section: Inbred Modelsmentioning
confidence: 99%
“…Mononuclear portal infiltrates Lobular hepatitis and perivascular infiltrates Antibodies to liver-specific protein T-cell vaccination experiments [97] Neonatal thymectomy Delayed hypersensitivity to liver-specific protein Decreased T regulatory cells [99] Cytokine induction IFN-g or TNF-a produce hepatocyte apoptosis TGF-b suppresses cytotoxic T cells [66,101,105] Concanavalin A T-cell induction…”
Section: Model Designmentioning
confidence: 99%
“…Retrospectively, these are very interesting because it has been shown by Asano et al [22] that neonatal thymectomy prevents the proper development of T reg . Therefore, their data suggest that liver-specific T cell-mediated autoimmune responses are controlled by the T reg population [21] . It is supposed that spontaneously developed autoimmune diseases are caused by a lack of functional regulatory activity by these cells.…”
Section: Models Of Experimental Aih Immunization Strategiesmentioning
confidence: 99%
“…A new aspect in EAH was brought in by Watanabe et al [21] when they found that histological hepatitis, the production of autoantibodies to LSP and delayed-type hypersensitivity to LSP were pronounced in mice after a neonatal thymectomy. The same was true for the disease after adoptively transferring the splenocytes.…”
Section: Models Of Experimental Aih Immunization Strategiesmentioning
confidence: 99%
“…The presence of liver autoantigen-specific T cells was demonstrated later by Lohse et al, who induced EAH by immunization of C57BL/6 mice with a crude 100,000 g supernatant of syngeneic liver homogenate (S-100) emulsified in complete Freund’s adjuvant [79]. Many follow-up studies used the S-100 injection model in various inbred mouse strains giving rise to valuable information on effector cells and regulatory phenomena in liver-specific immune reactions [80,81,82]. In addition, it has also become evident that an external trigger is required to induce acute and/or chronic hepatitis.…”
Section: Mechanistic Insight From Animal Modelsmentioning
confidence: 99%